(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The gold standard is the determination of CMV in cell culture. As a rule, human foreskin fibroblast cells are used for this purpose. Blood, urine, saliva, cervical-vaginal secretion, cerebrospinal fluid, BAL and tissue from biopsy specimens are the materials for the study. Reproduction of CMV in cell culture is accompanied by a characteristic CMV-associated cytopathic effect [7,8,9].